Randomized Clinical Trial: Probiotics Alleviated Oral-Gut Microbiota Dysbiosis and Thyroid Hormone Withdrawal-Related Complications in Thyroid Cancer Patients Before Radioiodine Therapy Following Thyroidectomy - Lin, Baiqiang; Zhao, Fuya; Liu, Yang; Wu, Xin; Feng, Jing; Jin, Xiangren; Yan, Wei; Guo, Xiao; Shi, Shang; Li, Zhiyong; Liu, Lujia; Chen, Hongye; et al. (Frontiers in Endocrinology, 2022)
Background: Thyroid hormone withdrawal (THW) in postoperative thyroid cancer patients who need always accompanied by complications (e.g., dyslipidemia and constipation). At present, there are no safe and effective means to alleviate these complications. Purpose: We aimed to assess the oral-gut microbiota profiles in THW patients then investigate whether probiotics could alleviating alleviate THW related complications and investigate whether these therapeutic effects were associated with the oral-gut microbiota state. Methods: Fifty eligible thyroid carcinoma patients undergoing thyroidectomy were randomly assigned to receive probiotics or placebo during THW. Complications were assessed through validated questionnaires and plasma lipid indicators. The complex probiotics preparation was composed of Bifidobacterium infantis, Lactobacillus acidophilus, Enterococcus faecalis, and Bacillus cereus. Results: Probiotics alleviated lack of energy, constipation, weight gain, and dry mouth and decreased the levels of plasma lipid indicators (total cholesterol, triglycerides, low-density lipoprotein, and apolipoprotein A) (P < 0.05). Gut and oral microbial diversity were significantly decreased after THW, while an increased microbial dysbiosis index (MDI) was observed. Probiotics distinctly restored the gut and oral microbial diversity. Increased Holdemanella, Enterococcus, and Coprococcus_2, while decreased Fusobacterium, Eubacterium_ruminantium_group, Ruminococcus_1, and Parasutterella in the gut were found after probiotics intervention. Lack of energy, constipation, weight gain, and dyslipidemia were seen to be related to the above microbiota. In addition, probiotics reduced oral Prevotella_9, Haemophilus, Fusobacterium, and Lautropia, which were positively correlated with the occurrence of dry mouth. Conclusion: Probiotics reduce the incidence of complications in patients after THW, which may be related to modifying the oral and gut microbiota.